Review Evaluation of Simalungun Regency Government Financial Reports - Purba, Efri Elsridayani; Martani, Dwi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The research aims to evaluate financial report examinations based on Government Regulation No. 4 of 2018 and analyze the quality of financial report examinations in Simalungun Regency. Despite compliance with regulations, the examination process could be more optimal as the review team did not assess SPI, conducted oral interviews without documented records, lacked questionnaires, and had a limited review period of ten days. This study was prompted by unqualified audit opinions in 2017-2018 and a need for information on obtaining unqualified audit opinions. The qualitative research employed a case study approach with descriptive analysis techniques, gathering data through document examinations, checklists, and interviews. Findings indicate that examining financial reports in Simalungun Regency followed Government Regulation No. 4 of 2018 but could be more optimal. Constraints include low reviewer competence and quantity, limited review time, and inadequate review training. The study concludes that the examination quality can be improved but is hindered by low reviewer competence and quantity, limited review time, and inadequate training. These insights highlight the need to enhance examination processes to ensure financial report reliability and accuracy, with recommendations for further research to explore audit opinions from external and internal perspectives and assess the role of APIP in enhancing financial report quality. These findings provide valuable contributions to financial governance improvement in Simalungun Regency and beyond.